Rasio Keuangan Mengungkap Kisah Tak Terungkap : Menilai Kinerja Perusahaan Setelah Boikot - Laila, Nurzannatul; Hijriah, Amanah; Damayanti, Fera (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
Ratios play a role in assessing how well a company is performing financially. Financial ratio analysis is a tool that involves examining financial indicators to track changes in a company's financial health. This research studies the performance of PT Mitra Adiperkasa, a company with ties to Israel focusing on liquidity, solvency, profitability, and activity ratios. In response to Israel's conflict with Gaza, there was a boycott campaign launched by Muslims in Indonesia. The purpose of this study is to evaluate how PT Mitra Adiperkasa performed after the boycott by using qualitative methods and horizontal analysis. Data from various sources is the basis of this research which examines the ratios of liquidity, solvency, profitability, and activity, for the years 2021-2022 the financial performance of PT Mitra Adiperkasa is in good condition. while in the years 2022-2023 the financial performance of PT Mitra Adiperkasa is not good. This proves that the boycott movement that was campaigned and became the peak of Muslim anger in 2023 affected the company's performance as assessed by the ratio.